Woodworking machineries: their operations, safety and hazards / Mohd Padli Saidin - Saidin, Mohd Padli (2001)
Using woodworking machine correctly is the important thing in furniture manufacturing. Each woodworking machine has different procedures and functions. Good safety procedure is the important thing to avoid accident. Although, there are many safety rules, accident still happened by years. It may be the user were careless in their job or called 'human nature mistake'. No proper instruction given to the worker and less knowledgeable also contributes this situation.